Volatile profile of white wines fermented with sequential inoculation of Starmerella bacillaris and Saccharomyces cerevisiae. (15th August 2018) - Englezos, Vasileios; Rantsiou, Kalliopi; Cravero, Francesco; Torchio, Fabrizio; Pollon, Matteo; Fracassetti, Daniela; Ortiz-Julien, Anne; Gerbi, Vincenzo; Rolle, Luca; Cocolin, Luca
Highlights: Mixed fermentations were tested for white wine production. Mixed fermented wines had diverse flavour profiles compared to pure fermented wines with S. cerevisiae . Wines produced from mixed culture fermentations did not show negative flavour profiles. Inoculation protocol influenced the aroma profiles of wines in a variety-dependent manner. Sauvignon blanc wines fermented by mixed cultures contained significantly higher levels of thiols. Abstract: Mixed fermentations with Starmerella bacillaris and Saccharomyces cerevisiae affect the chemical composition of wines, by modulating various metabolites of oenological interest. The current study was carried out to elucidate the effect of sequential inoculation of the above mentioned species on the production of white wines, especially on the chemical and aromatic characteristics of Chardonnay, Muscat, Riesling and Sauvignon blanc wines. Titratable acidity and glycerol content exhibited evident differences among the wines after fermentation. For volatile compounds, mixed fermentations led to a reduction of the total esters, including ethyl acetate, which is a compound responsible for wine deterioration. However, Sauvignon blanc wines fermented by mixed cultures contained significantly higher levels of esters and thiols, both associated with positive sensory attributes. These findings suggest that sequential inoculations possess great potential in affecting and modulating the chemical and aromatic profile of white wines, especially those produced from Sauvignon blanc grapes.